Attitudes to various areas of physical culture in view of indoor and outdoor physical education lessons - Mirosława Szark-Eckardt; Marcin Pasek (Kazimierz Wielki University, 2017)
In times of increased expansion of modern technologies, there is still the debate about the health condition of the young generation being increasingly keen on the lifestyle characterised by physical passivity combined with commitment to virtual entertainment. A change in this reality depends, among other things, on physical education teachers who have an opportunity to increase activity of their students already at the level of fostering desirable attitudes towards physical culture. In addition to personality of the teachers, new innovation projects set up as part of physical education at school are more likely to be critical to the success of these measures. The aim of this study was a comparative assessment of attitudes within individual areas of physical culture in the course of indoor and outdoor physical education classes. The pedagogical experiment was attended by 220 students, out of whom 103 subjects accounted for the experimental group and 117 for the control group. The questionnaire of attitudes to physical culture was used as a research tool and consisted of 67 questions belonging to 10 various physical culture areas. The final findings suggested a significant improvement in the attitudes of both groups compared to the initial study. This progress was noticeable in the experimental group to a greater extent. The effects of the conducted experiment confirm the purpose of implementing innovation in the education system and in relation to this research, they indicate an important role of the natural environment as a basis for developing attitudes intended to enhance an engagement in physical culture at later life stages.